Self-Balancing Position-Sensitive Detector (SBPSD) - Ryan Porrazzo; Leigh Lydecker; Suhasini Gattu; Hassaram Bakhru; Natalya Tokranova; James Castracane (Sensors, 2015)
Optical position-sensitive detectors (PSDs) are a non-contact method of tracking the location of a light spot. Silicon-based versions of such sensors are fabricated with standard CMOS technology, are inexpensive and provide a real-time, analog signal output corresponding to the position of the light spot. An innovative type of optical position sensor was developed using two back-to-back connected photodiodes. These so called self-balancing position-sensitive detectors (SBPSDs) eliminate the need for external readout circuitry entirely. Fabricated prototype devices demonstrate linear, symmetric coordinate characteristics and a spatial resolution of 200 μm for a 74 mm device. PSDs are commercially available only up to a length of 37 mm. Prototype devices were fabricated with various lengths up to 100 mm and can be scaled down to any size below that.